Penal Protection for the Establishement Creditors [In Arabic] - Nekkache, Hamza; Boulares, Ahmed (Milev Journal of Research and Studies, 2022)
The property of the company, whateveritsform and nature, is of great importance becauseitis the guarantor of the continuity of itsactivityuntil the stage of itsbankruptcy and liquidation. Therefore, wefindthat the legislationdistinguishedhim a unique protection in order to preserve the financial information of the company not only to protect the company and the right of itsassociates, but also to protect the group of creditorshavingdealtwith the company of the abuses whichcouldbecommitted by thoseresponsible for management, includingofficers or managers, as the case maybe.